Psychological Characteristics Of Stress Tolerance Formation Of Young Leaders In Uzbekistan - Lola Inagamova (Goodwood Publishing, 2026)
Purpose: The main problem put forward in this study is to determine the socio-psychological characteristics of the formation of stress tolerance in young managers. Based on this goal, the levels of manifestation of stress tolerance in a young manager were studied. Research Methodology: A socio-psychological questionnaire was developed and conducted to determine stress tolerance in young managers. The questionnaire consisted of four blocks: the causes of stress, emotional experiences, thoughts about the consequences of stress, and strategies for managing stress. The research was conducted with participants from the leadership training program at the Academy of Public Administration in Uzbekistan. Results: The study found that 36.2% of respondents believe that lack of sleep, 12.0% have headaches, and 24.8% lack of mood as the primary stress factors. Additionally, 11.1% of young leaders consider the negative attitude of colleagues, 25.1% excessive fatigue, and 10.3% lack of peace in the family as stress-inducing factors. Conclusions: The findings highlight the importance of stress tolerance in enhancing the leadership qualities of young managers. Effective stress management can improve work efficiency, reduce the incidence of illness, and lead to better communication and leadership. Limitations: The study was limited to a specific group of young managers in Uzbekistan, and the findings may not be applicable to other regions or contexts. Contributions: This study contributes to the understanding of stress management and its role in developing effective leadership qualities in young managers, with implications for leadership training programs.